PENDIDIKAN SEKS DALAM ISLAM; Suatu Upaya Pembebasan Tindak Kekerasan Seksual Remaja - Wahyudi, Arif (KARSA Journal of Social and Islamic Culture, 2012)
Abstract In Indonesia, public regard sex as something natural. Sex is god’s omnipotence, hence it is not important to communicate it to children and teenagers. They will know the information about sex as soon as they grow older. However the rapid growth of mass media, puts many parents in a dilema. How the parents protect the children from the trap of cultural sexuality values, and social reality values particularly from the case of sexual harshment. One of the ways to protect them is by socializing sex education earlierly. It is to let the teenagers have sufficient knowledge of sex. Kata-kata kunci remaja, pendidikan seks, kekerasan seksual